1995
DOI: 10.1007/bf01791145
|View full text |Cite
|
Sign up to set email alerts
|

Renal and extrarenal clearance of99mTc-MAG3: A comparison with125I-OIH and51Cr-EDTA in patients representing all levels of glomerular filtration rate

Abstract: . This investigation was undertaken in order to determine whether the clearance of technetium-99m mercaptoacetyltriglycine (99mTc-MAG3) is more closely correlated to the clearance of iodine-125 orthoiodohippurate (125I-OIH) than to the clearance of chromium-51 ethylene diamine tetra-acetate (51Cr-EDTA) and whether there is a clinically significant extrarenal clearance of 99mTc-MAG3 . Fifty-one patients with a glomerular filtration rate (GFR) of 4-132ml/min were studied. After a simultaneous single injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 12 publications
2
26
0
1
Order By: Relevance
“…The higher degree of binding to plasma protein of [ 99m Tc]MAG 3 compared with that of [ 131 I]OIH can explain the [3,21,23]. Both compounds are extracted mainly by tubular secretion; thus, the lower renal extraction fraction for [ 99m Tc]MAG 3 may be related to its slower dissociation from binding sites (blood proteins) or to a lower affinity for the tubular transport system compared with [ 131 I]OIH.…”
Section: Discussionmentioning
confidence: 99%
“…The higher degree of binding to plasma protein of [ 99m Tc]MAG 3 compared with that of [ 131 I]OIH can explain the [3,21,23]. Both compounds are extracted mainly by tubular secretion; thus, the lower renal extraction fraction for [ 99m Tc]MAG 3 may be related to its slower dissociation from binding sites (blood proteins) or to a lower affinity for the tubular transport system compared with [ 131 I]OIH.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, 10 blood samples (5,12,17,27,37,44, 60, 90, 120 and 180 min post-injection) of 5 ml were drawn into heparinized tubes through an indwelling catheter with a three-way stopcock from the contralateral arm; the catheter was rinsed with saline after each blood sampling. Subsequently, 10 blood samples (5,12,17,27,37,44, 60, 90, 120 and 180 min post-injection) of 5 ml were drawn into heparinized tubes through an indwelling catheter with a three-way stopcock from the contralateral arm; the catheter was rinsed with saline after each blood sampling.…”
Section: Clearance Measurementmentioning
confidence: 99%
“…The utility of 99m Tc-MAG3 clearance has been extensively investigated in several studies [4][5][6], and it has been shown that the clearance of 99m Tc-MAG3 is closely correlated with the clearance of [ 131 I]OIH [6][7][8][9]. However, it has generally been reported that, although 99m Tc-MAG3 has very good accuracy [7][8][9][10][11][12], the results in terms of reproducibility are still controversial [13][14][15][16][17][18][19]. The reproducibility of the study is especially important in patients with renal failure in order to determine whether changes in renal function in serial measurements are related to progression, regression, resolution of the disease or poor reproducibility of the test.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the authors consider that 51 Cr-EDTA is not binding to proteins (<0,5% (Brochner-Mortensen, 1978;Bailey et al, 1970;Garnett et al, 1967;Stacy & Thorburn, 1966;Forland et al, 1966;Kempi & Persson, 1975;Forland et al, 1966)) even if Rehling described a binding to protein of 10% (Rehling et al, 1995;Rehling et al, 2001). Due to its low molecular weight, 51 Cr-EDTA is freely filtrated through the glomerulus.…”
mentioning
confidence: 99%
“…Jagenburg had also calculated an extra-renal clearance of 2 mL/min in two anuric dialysis patients (Jagenburg et al, 1978). Only, Rehling described a higher extra-renal clearance at 8.4% (Rehling et al, 1995). Measurement of 51 Cr-EDTA by nuclear count is very precise and easy because 51 Cr-EDTA half time is long (27 days) (Chantler et al, 1969).…”
mentioning
confidence: 99%